The Existence Of Unit Link Products : Empirical And Juridical Review - Firman Syah, Ardy; Saleh, Ilham (Faculty of Islamic Economics and Business, Madura Islamic State University, 2025)
The purpose of this study is to obtain strategic steps for business actors in limiting the sale of unit-linked products based on the latest regulations through the factor analysis method. The methodology used is descriptive analysis with a qualitative approach. The literacy sources used come from primary data, namely literature reviews, mass media and applicable laws and regulations as well as secondary data on the Statement Of Financial Position from the Financial Services Authority to be further studied in measuring the parameters of the analysis of policy recommendations needed next. The results of the study show that the high level of risk in marketing unit-linked products with the PAYDI system is still limited by the placement of investment funds that are medium risk, insurance sector business actors can provide recommendations on the placement of funds made by customers based on the quality of the investment manager's portfolio and investment categories that are not based on high risk. Fixed unit link products provide an appropriate margin for business actors through periodic top up administration fees. The element of protection from cash value remains the basis of the priority of this unit link marketing.